Studi Kekuatan Sambungan Komposit Laminasi Kayu Mahoni Dengan Perekat PVAc Setelah Paparan Air Distilasi, Air Laut, dan Minyak Sayur - Burhani, Ichwan; Permana Pinem, Mekro; Ula, Shofiatul; Saefuloh, Iman; Sunardi, Sunardi (Jurnal Inovasi Teknologi Terapan, 2025)
Laminated composites are composed of multiple layers that work together to achieve specific properties. Several factors influence the strength of these composites, including the quality of the surface layers, the strength of the bonds between layers, the adhesion properties, and the thermal behavior. The adhesive plays a crucial role in connecting the layers to form a laminated composite. This study investigates the effect of environmental exposure on the bond strength between the surfaces of laminated composite layers. The laminated composites are made from mahogany wood and are adhered using PVAc adhesive under a pressure of 2 MPa for 30 minutes. After being prepared, the samples are allowed to sit for several days before being immersed in distilled water, seawater, and vegetable oil. Each immersion lasts for 24 hours. The results indicate that the laminated composites experienced a degradation of mechanical properties following exposure to distilled water, seawater, and vegetable oil. Among these, distilled water had the most detrimental effect on the performance of the laminated composite, while exposure to vegetable oil resulted in relatively insignificant changes to its mechanical properties.